Glycogen Storage Disease Type Ib in the Compound Heterozygous State: Case Report - Nikol P. Shimkova; Mariya A. Snegurenko; Eva Yunkevich; Nataliya V. Klimina; Anastasiya A. Shepina; Lyubov E. Larina (Педиатрическая фармакология)
Background. Glycogen Storage Disease Type Ib (GSDIb) is an inherited autosomal recessive orphan disease associated with a deficiency of the glucose—6-phosphate translocase transport protein and leading to excessive accumulation of glycogen in the liver and other organs. GSDIb occurs in about 20% of patients with type I glycogenosis and is characterized by a variety of manifestations, which makes diagnosis difficult.Case report: A clinical example of early diagnosis of GSDIb in a 5-month-old boy with a burdened perinatal history is presented. The disease was suspected due to the presence of persistent neutropenia and hypoglycemia in the child, as well as recurrent bacterial infections. Whole-exome sequencing was performed, on the basis of which the diagnosis was made: “GSDIb caused by variants in the SLC37A4 gene: c.1108_1109delCT p.Leu370fs and c.85A>G p.Lys29Glu in a compound heterozygous state”.Conclusion. The presented case report highlights the need for early diagnosis of GSDIb. This will allow timely initiation of specific therapy and improve the prognosis for patients with this disease.